A deep intronic SMARCB1 variant associated with schwannomatosis. Issue 2 (9th September 2019) - Smith, Miriam J.; Bowers, Naomi L.; Banks, Catherine; Coates‐Brown, Rosanna; Morris, Katrina A.; Ewans, Lisa; Wilson, Meredith; Pinner, Jason; Bhaskar, Sanjeev S.; Cammarata‐Scalisi, Francisco; Wallace, Andrew J.; Evans, Daffyd Gareth R.
Abstract :